2021
DOI: 10.1186/s13287-021-02318-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled clinical trial of autologous stromal vascular fraction cells transplantation to promote mechanical stretch-induced skin regeneration

Abstract: Background The regeneration response of the skin to mechanical stretching in vivo has been explored in reconstructive surgery to repair large-scale deformities. The ability of the skin to regenerate limits the reconstructive outcome. Here, we propose an approach in which autologous stromal vascular fraction (SVF) cells and mechanical stretching are combined to overcome this limitation and promote skin regeneration. Methods This randomized, blinded,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…Soft-tissue expansion by mechanical stretching represents an efficient surgical procedure for skin-defect repair and organ reconstruction; however, the skin-regenerative capacity is limited ( 2 ). Stem cell therapy represents an alternative method for enhancing the regeneration of mechanically stretched skin ( 2 5 ). In particular, ESCs and HFBSCs located in situ play a vital role in skin regeneration and repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft-tissue expansion by mechanical stretching represents an efficient surgical procedure for skin-defect repair and organ reconstruction; however, the skin-regenerative capacity is limited ( 2 ). Stem cell therapy represents an alternative method for enhancing the regeneration of mechanically stretched skin ( 2 5 ). In particular, ESCs and HFBSCs located in situ play a vital role in skin regeneration and repair.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple biological behaviors, including cell proliferation, dermal collagen synthesis, and angiogenesis, influence skin regeneration during the mechanical stretching process. Previous studies show that stem cell therapy using bone marrow-derived stem cells and/or adipose-derived stem cells promotes mechanically stretched skin regeneration ( 2 5 ). However, skin-derived stem cells, especially epidermal stem cells (ESCs) and hair follicle bulge stem cells (HFBSCs) ( 6 ), might also perform critical regenerative functions during skin expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al transplanted SVF into the expanded skin of Wistar rats and found that SVF significantly improved the expansion efficiency and up-regulated the expressions of EGF, VEGF, and bFGF [ 134 ]. Recently, a randomized, controlled clinical trial of autologous stromal vascular fraction cells transplantation was conducted [ 135 ]. In this study, twenty patients participated in the trial and the results showed that the expanded skin receiving SVF grafts was thicker and more proliferating cells, more blood vessels, and more extracellular matrix were observed.…”
Section: Cellular Mechanismmentioning
confidence: 99%
“…Both BMSC- and ADSC-induced skin growth and regeneration have been clinically tested and shown satisfactory results in skin expansion [ 135 , 156 ]. After BMSC and ADSC transplantation in patients, the expanded skin showed larger area, thicker epidermis and dermis, more blood vessels, and higher expansion index (EI).…”
Section: Cellular Mechanismmentioning
confidence: 99%
“…4 Although drugs, such as anticontractile agents, papaverine, and dimethyl sulfoxide, have been studied for promoting the expansion course, these have caused additional complications. [5][6][7] We previously reported that stem cell therapies could effectively promote stretching-induced skin regeneration 8,9 ; however, harvesting stem cells caused additional damage to the body.…”
mentioning
confidence: 99%